Adhesive contact of a diamond sphere with an iron substrate caused by interatomic interaction. (December 2020) - Zeng, Yi; Wang, Zhanjiang; Qin, Na; Jiang, Liang; Du, Wenhao; Qian, Linmao
By incorporating the adhesive force as a body force in the finite element method, the adhesive contact between a diamond sphere and the iron substrate is studied. The adhesive force is derived from Morse potential by integrating the pair potential function over the spherical domain. Based on the tensile behaviors of iron nanowires, the elastic and elastoplastic material parameters are obtained for the substrate. As the radius of the sphere is larger than 320 nm and the maximum depth of indentation is one-tenth of the radius of the sphere, the adhesion caused by interatomic interaction between diamond and iron is small enough to ignore. Then take the sphere whose radius is 20 nm as an example, the results of a single load–unload cycle and multiple load–unload cycles are discussed. In the contact process between the sphere and the surface, the phenomena jump-to-contact and jump-off-contact were observed. Further, the stress distributions inside the substrate and the pressure distribution are investigated. With the analysis of the results, the proposed method can be used to simulate the mechanical behaviors under micro-nano scale contact.